PEMANFAATAN BUAH NIPAH DAN BUAH PEPAYA DALAM PEMBUATAN FRUIT LEATHER - Hirdan, Hirdan; Pato, Usman; Rossi, Evy (Fakultas Pertanian Universitas Riau, 2021)
Fruit leather is a type of food made from fruit meat that has been crushed and dried, so it forms a thin sheet that can be rolled. The purpose of this research was to get the best combination of palm puree and papaya puree in making fruit leather. This research was experimental conducted by using complete randomized design (CRD) which consists of five treatments and three replications. The treatments in this research were NP1 (palm puree and papaya puree 65:35), NP2 (palm puree and papaya puree 55:45), NP3 (palm puree and papaya puree 50:50), NP4 (palm puree and papaya puree 45:55), and NP5 (palm puree and papaya puree 35:65). The data obtained were statically analyzed using Analysis of Variance (ANOVA) and continued with Duncan New Multiple Range Test at the 5% level. The data of fruit leather showed that ratio of palm puree and papaya puree significantly affected pH value moisture, ash and crude fiber content, total dissolved solids, sensory test of color, flavour, taste, and texture. The best treatment from this research was NP5 (palm puree and papaya puree 35:65) with pH level 4.26, moisture content 10.01%, ash 0.73%, crude fiber contents 1.71%, total dissolved solids 26.08%, and, orange color (4.50), papaya flavour (4.13), taste sweet (3.83), the texture rather springy (3.00), and overall assessment of fruit leather was liked by the panelist (3.91).